ANALYSIS OF THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY IN PREVENTING WORK ACCIDENTS IN PT PELABUHAN INDONESIA I (PERSERO) BELAWAN BRANCH - Adinda Surya Putri; Harmein Nasution; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Based on previous explanations, this research finally provides the following conclusions: Management's commitment to implementing occupational health and safety is significantly related to employee work accidents at PT Pelabuhan Indonesia I (Persero) Belawan Branch. The relationship between management commitment and work accidents is a negative relationship with a relationship size of 0.314, meaning that when management commitment is increased, the possibility of work accidents can be avoided or reduced by 0.314 times. 2. Implementation of occupational health and safety in the company's work environment is significantly related to employee work accidents at PT Pelabuhan Indonesia I (Persero) Belawan Branch. The relationship between the work environment and work accidents is a negative relationship with the magnitude of the relationship being 0.405, meaning that when the work environment is improved, the possibility of work accidents can be avoided or reduced by 0.405 times. 3. Work health and safety procedures are significantly related to employee work accidents at PT Pelabuhan Indonesia I (Persero) Belawan Branch. The relationship between occupational health and safety procedures and work accidents is a negative relationship with a relationship size of 0.409, meaning that when work health and safety procedures are improved, the possibility of work accidents can be avoided or reduced by 0.409 times. 4. Employee training in implementing occupational health and safety is significantly related to employee work accidents at PT Pelabuhan Indonesia I (Persero) Belawan Branch. The relationship between occupational health and safety training and occupational accidents is a negative relationship with a correlation size of 0.386, meaning that when occupational health and safety training is improved, the possibility of occupational accidents can be avoided or reduced by 0.386 times.